HUBUNGAN PENGETAHUAN REMAJA PUTRI DENGAN PERAN ORANG TUA MENGENAI HOT HERBAL COMPRESS DI SMKK PRIMA INDONESIA - Siti Muslima W Udi; Anisa Az-Zahrah (Jurnal Ilmiah Kebidanan Imelda, 2021)
Painful menstruation is a symptomatic phenomenon, including abdominal cramps, backache and pain.The only traditional treatment Is Hot Herbal Compress. Hot Herbal Compress is a tool and material used as a hot compress which containseffect as a pain reliever and provide relaxation that comes from the aroma of these natural ingredients.Indonesian Health Demographic Survey (2017), 76% of adolescent experienced menstrual pain during menstruation, 58% of female adolescents who did not experience menstrual pain during menstruation. This study aims to determine therelationship between knowledge of adolescent with the role of parents regarding hot herbal compress to relieve painful menstruation. This type of analytic research with cross sectional approach. The sampling technique used purposive sampling involving 40 adolescent at SMKK Prima Indonesia and the results showed that most of the knowledge of adolescent about hot herbal compresses to relieve painful menstruation was less (52.5%) and based on the role of parents regarding hot herbal compresses. To relieve painful menstruation most did not participate (57.5%). There is a relationship between the knowledge of adolescent knowledge and the role of parents regarding hot herbal compresses to relieve painful menstruation at SMKK Prima Indonesia in 2020 with a p value = 0.000